Clinical Outcomes and Toxicity Profile of Cetuximab-Containing Regimen in Locoregionally Recurrent and Metastatic Head and Neck Squamous Cell Carcinoma: A Single-Institution Retrospective Audit - Tryambake, Siddhesh Rajendra; Nirni, Sharanabasappa Somanath; Andhra, Vindhya Vasini; Reddy, Ch. Shyny; Bathula, Surendra (Indian Journal of Medical and Paediatric Oncology, 2025)
Recurrent or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) remains one of the most prevalent and challenging malignancies worldwide. The combination of cetuximab and chemotherapy continues to be a preferred therapeutic option for these patients. However, despite extensive research aimed at optimizing this combination, the median overall survival (OS) remains limited to approximately 1 year. Long-term survival outcomes continue to be dismal, highlighting the urgent need for more effective treatment strategies and real-world data to guide clinical decision-making.The aim of this study is to evaluate the differential effectiveness of cetuximab-containing treatment in locoregional recurrence versus distant metastasis and identify clinical factors associated with improved survival in patients with R/M SCCHN.This retrospective study included patients with histopathologically confirmed R/M SCCHN, staged according to the Union for International Cancer Control TNM classification and American Joint Committee on Cancer seventh edition. Eligible patients were ≥18 years old, had locoregional recurrence or distant metastasis, an ECOG (Eastern Cooperative Oncology Group) performance status of 0 to 2, and no contraindications to treatment. All patients received cetuximab-based treatment during the defined study period. Study endpoints included OS, progression-free survival (PFS), overall response rate (ORR), and disease control rate (DCR). Response was assessed using RECIST 1.1 criteria after at least three cycles or earlier if clinically indicated. Safety was evaluated based on CTCAE v5.0 criteria.A total of 100 patients (median age: 56.5 years) with R/M SCCHN received cetuximab-based chemotherapy. In the overall population, the median OS was 19 months (95% confidence interval [CI]: 17.1–20.9), with 1- and 2-year OS rates of 77.9 and 33%, respectively. Median PFS was 3 months (95% CI: 2.7–3.3), with 3- and 6-month PFS rates of 34.7 and 12.6%, respectively, and tumor responses indicated meaningful disease control (ORR: 37%; DCR: 55%). Patients with locoregional recurrence had significantly longer OS than those with distant metastasis (23 vs. 17 months, p = 0.01). Treatment was well-tolerated.Cetuximab-based therapy is more effective in achieving disease control and survival in patients with SCCHN who have locoregional recurrence, compared with those with distant metastases.
Keywords: advanced SCCHN; cetuximab-based treatment; distant metastasis; recurrent disease; survival outcomes; toxicity profile